Relationships between Body Mass Index, Nutritional Intakes, and Living Arrangement with Menstrual Cycle among Students - Indriani, Aliza Umar; Annas, Jimmy Yanuar; Herawati, Lilik (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Disorders of the menstrual cycle are common in women aged 18-26 years. Indonesian Basic Health Research year 2013 data shows that as many as 13.7% of women of reproductive age experience problems with irregular menstrual cycles. Disturbances in the menstrual cycle can cause infertility and decrease the quality of life of students. The purpose of this study was to determine the relationship between body mass index (BMI), nutritional intake patterns, and living arrangements with the menstrual cycle of female students. Subjects and Method: A cross-sectional study was conducted at the Faculty of Medicine, Airlangga University, from July to September 2022. A total of 176 female students from the Faculty of Medicine, Airlangga University, class of 2018-2021 were selected using a purposive sampling technique. The dependent variable is the menstrual cycle. The independent variables are body mass index (BMI), patterns of nutritional intake, and living arrangements. The instrument used in this research is a questionnaire. Research data were analyzed using binary logistic regression. Results: Overweight BMI (OR= 49.32; 95%CI= 9.57 to 254.35; p<0.001) and patterns of excess nutrition (OR= 28.69 95%CI= 4.97 to 165.94; p<0.001) have a relationship with female students' menstrual cycles Faculty of Medicine, Airlangga University Conclusion: Overweight BMI and nutritional intake patterns together have a relationship to the menstrual cycle of female students at the Faculty of Medicine, Airlangga University. Keywords: body mass index, pattern of nutritional intake, living arrangement, menstrual cycle Correspondence: Aliza Umar Indriani, Faculty of Medicine, Universitas Airlangga. Jl. Mayjen Prof. Dr. Moestopo No. 47, Tambaksari, Surabaya 60132, East Java. Email: aliza.umar.indriani-2019@fk.unair.ac.id. Mobile: +6281252337795.